Implementasi konsep Tzkiyatun Nafs dalam pendidikan islam - Agus Sopian; Akhdiyat Nazriel Fauzan; Julian Iqbal Muntaha; Muhamad Vicky Pandanu; Ismail Mubarok (CV. ITTC INDONESIA, 2026)
Islamic education aims not only to develop students' intellectual abilities but also to cultivate moral character and spirituality based on Islamic values. One of the key concepts supporting this objective is Tazkiyatun Nafs, which refers to the purification of the soul through moral development, self-control, and strengthening one's relationship with Allah. This study aims to analyze the implementation of the Tazkiyatun Nafs concept in Islamic education through a synthesis of previous studies. The research employed a Systematic Literature Review (SLR) using a qualitative approach by analyzing nine scholarly articles related to Tazkiyatun Nafs, character education, and Islamic education. The findings indicate that the implementation of Tazkiyatun Nafs is carried out through habituation of religious practices, teachers' role modeling, the development of a religious school culture, the integration of Islamic values into the learning process, and collaboration among schools, families, and communities. These practices contribute positively to the development of students' religious character, self-control, discipline, responsibility, social awareness, and spiritual intelligence. However, the implementation of Tazkiyatun Nafs still faces challenges, including rapid digital technological development, social environmental changes, and the predominance of academic achievement over character development in educational practices. Therefore, the continuous implementation of Tazkiyatun Nafs is considered a relevant strategy for achieving the objectives of Islamic education in developing individuals who are knowledgeable, faithful, and possess noble character.